Marine debris in Malaysia: A review on the pollution intensity and mitigating measures. (June 2021) - Fauziah, Shahul Hamid; Rizman-Idid, Mohammed; Cheah, Wee; Loh, Kar-Hoe; Sharma, Sahadev; M.R, NoorMaiza; Bordt, Michael; Praphotjanaporn, Teerapong; Samah, Azizan Abu; Sabaruddin, Johan Shamsuddin bin; George, Mary
Abstract: The launch of Roadmap towards Zero Single-use Plastics in 2018 demands baseline data on the management of marine debris in Malaysia. In 2021, Malaysia is placed 28th top plastic polluter in the world with plastic consumption at 56 kg/capita/year, therefore data on mismanaged plastic is imperative. This paper reviews the abundance and distribution of marine debris in selected Malaysian beaches over the last decade (2010–2020) and discusses issue on its management. Plastic debris on beaches in Malaysia, was reported to range from 64 items/m 2, to as high as 1930 items/m 2, contributing 30–45% of total waste collected. Plastics film was the most dominant, mainly originated from packaging materials. Therefore, appropriate action including improved marine waste management system is crucial to tackle the problem, together with effective governance mechanisms. Various suggestions were proposed based on the statistical-environmental data to reduce the occurrence of marine debris in the country. Highlights: Studies on marine debris in Malaysia are gaining attention over the past two years due to change of policy by the government. Baseline data on marine debris pollution is fundamental to coastal ecosystem health. Natural and synthetic polymers dominated the types of marine debris along the Malaysian beaches, at more than 84%. Plastic packaging is the main type of plastic debris accumulated on the beach. Marine debris was also recorded in isolated and non-habitable islands in Malaysia.